A Comparative Evaluation of Cardiothoracic Radiology Fellowship Website Content. Issue 3 (May 2020) - Gibney, Brian; Redmond, Ciaran E.; Niu, Bonnie; Hamid, Saira; Kim, Gio; O'Neill, Siobhán B.; Khosa, Faisal
Abstract : Purpose: Prospective radiology fellows often rely on the internet to obtain information with regard to the application process for and the unique qualities of different fellowship programs. The aim of this study was to analyze the content of websites of the United States' and Canadian cardiothoracic radiology fellowships. Methods: All active Cardiothoracic Radiology fellowship websites as of July 2019 were evaluated and compared using 25 criteria in the following domains: Application, Recruitment, Clinical Training, Education/Research, and Incentives. Program website information availability was compared by geographic region. Results: There were 60 active cardiothoracic radiology fellowships, and 59 of these fellowships had a dedicated fellowship website. Websites, on average, had 9.3 of the 25 criteria (37.2%). The mean number of schools that satisfied the criterion in the "Incentives" domain ([7.75/59] 10.5%±2.8%) was significantly lower than that for the "Application Process" domain ([40.50/59]; 68.7%±40.6%) ( P =0.01). There was no significant difference in the information content of programs in different geographic regions ( P =0.246). Conclusion: Most cardiothoracic radiology fellowship websites were lacking content relevant to prospective fellows. Provision of more relevant and easily accessible online content may support programs to better inform and recruit residents and to promote the specialty of cardiothoracic radiology.